Blueprint for an Undergraduate Primary Care Curriculum. (December 2016) - Fazio, Sara B.; Demasi, Monica; Farren, Erin; Frankl, Susan; Gottlieb, Barbara; Hoy, Jessica; Johnson, Amanda; Kasper, Jill; Lee, Patrick; McCarthy, Claire; Miller, Kathe; Morris, Juliana; et al.
Abstract : In light of the increasing demand for primary care services and the changing scope of health care, it is important to consider how the principles of primary care are taught in medical school. While the majority of schools have increased students' exposure to primary care, they have not developed a standardized primary care curriculum for undergraduate medical education. In 2013, the authors convened a group of educators from primary care internal medicine, pediatrics, family medicine, and medicine–pediatrics, as well as five medical students to create a blueprint for a primary care curriculum that could be integrated into a longitudinal primary care experience spanning undergraduate medical education and delivered to all students regardless of their eventual career choice. The authors organized this blueprint into three domains: care management, specific areas of content expertise, and understanding the role of primary care in the health care system. Within each domain, they described specific curriculum content, including longitudinality, generalism, central responsibility for managing care, therapeutic alliance/communication, approach to acute and chronic care, wellness and prevention, mental and behavioral health, systems improvement, interprofessional training, and population health, as well as competencies that all medical students should attain by graduation. The proposed curriculum incorporates important core features of doctoring, which are often affirmed by all disciplines but owned by none. The authors argue that primary care educators are natural stewards of this curriculum content and can ensure that it complements and strengthens all aspects of undergraduate medical education. Abstract : Supplemental Digital Content is available in the text.